Final state resolved mutual neutralization of Li+ and D−. Issue 23 (January 2020) - Eklund, G; Grumer, J; Rosén, S; Najeeb, P K; Zettergren, H; Cederquist, H; Barklem, P S; Schmidt, H T
Synopsis: We have performed a merged beam experiment on mutual neutralization of Li + and D −, at center of mass energies close to 0 eV using the DESIREE storage rings. The final state channels Li(3s) and Li(3p+3d) are resolved and the branching ratio is found to be more equal than predicted from theoretical models.